Eksplorasi Dampak Chatbot Bertenaga AI (ChatGPT) Pada Pendidikan: Studi Kualitatif Tentang Manfaat dan Kerugian - Subiyantoro, Singgih; Degeng, I Nyoman Sudana; Kuswandi, Dedi; Ulfa, Saida (Jurnal Pekommas, 2023)
The advancement of technology has driven the implementation of artificial intelligence-based chatbots in various fields, including education. This research investigates the impact of the presence and usage of AI-powered chatbots (Chat GPT) in the field of education, with a focus on potential benefits and drawbacks. The study employs a qualitative approach, gathering data through in-depth interviews and participatory observations in multiple educational institutions. Additionally, responses and perspectives from educators, students, and administrative staff are obtained through structured questionnaires. This research reveals that using AI-powered chatbots in education brings several benefits, such as improving the accessibility of learning materials, providing personalized learning support, and addressing individual challenges in the teaching and learning process. However, on the other hand, there are some drawbacks, including the potential replacement of essential social interactions between teachers and students and concerns regarding privacy issues and ethical use of data. Based on these findings, this study concludes that implementing AI-powered chatbots in education can provide significant benefits but also requires careful consideration of potential negative impacts. Overall, this article provides a profound understanding of how AI-based chatbots can be valuable tools in supporting the teaching and learning process while identifying aspects that need to be considered to optimize benefits and minimize risks in their usage.